Electronic Structure Engineering of Honeycomb Layered Cathode Material for Sodium‐Ion Batteries. Issue 14 (22nd February 2021) - Voronina, Natalia; Kim, Hee Jae; Konarov, Aishuak; Yaqoob, Najma; Lee, Kug‐Seung; Kaghazchi, Payam; Guillon, Olivier; Myung, Seung‐Taek
Abstract: In this work, the rational design of O′3‐type Na[Ni2/3− x Co x Sb1/3 ]O2, a solid solution of Na[Ni2/3 Sb1/3 ]O2 –Na[Co2/3 Sb1/3 ]O2, is introduced. Because of the difficulty of the Co 3+/2+ redox reaction, the electronic structures of Na[Ni2/3− x Co x Sb1/3 ]O2 compounds are engineered to build electroconducting networks in the oxide matrix through electrochemical oxidation of Co 2+ to Co 3+, after which the formed Co 3+ does not participate in the electrochemical reaction but improves the electrical conductivity in the structure. Density functional theory calculations reveal a reduced bandgap energy after the formation of Co 3+ during desodiation of Na1− y [Ni2/3− x Co x Sb1/3 ]O2 . Using the oxidized Co 3+ species while improving the electrical conductivity, the Na[Ni2/3− x Co x Sb1/3 ]O2 ( x = 1/6) electrode exhibits excellent cyclability for 1000 cycles with ≈72.5% capacity retention at 2C (400 mA g −1 ) and activity even at 50C (10 A g −1 ) in Na cells. Operando X‐ray diffraction and ex situ X‐ray absorption near‐edge structure investigations reveal suppressed lattice variations upon charge and discharge compared with those of Na[Ni2/3 Sb1/3 ]O2 achieved by the presence of the electrochemical‐driven Co 3+ in the structure. These findings offer a new strategy for the development of cathode materials for sodium‐ion batteries, providing important insight into their structural transformations and the electronic nature of advanced cathode materials. Abstract : The electronic structure of honeycomb layered Na[Ni2/3−x Cox Sb1/3 ]O2 is engineered as a cathode material for sodium‐ion batteries. The results emphasize that the electrochemically driven Co 3+, which does not participate in the electrochemical reaction, not only enhances electrical conductivity but aids structural stabilization to suppress volume variation, leading to excellent long‐term cyclability.